2018
DOI: 10.1016/j.bbr.2018.04.046
|View full text |Cite
|
Sign up to set email alerts
|

Effects of HIV-1 TAT protein and methamphetamine exposure on visual discrimination and executive function in mice

Abstract: Mild neurocognitive impairments are common in people with human immunodeficiency virus (HIV) infection. HIV-encoded proteins, such as trans-activator of transcription (TAT), contribute to neuropathology and cognitive function in medicated subjects. The combination of TAT and comorbid methamphetamine use may further impair neurocognitive function in HIV-positive individuals by affecting dopaminergic systems in the brain. The current study examined the effects of TAT protein expression and methamphetamine exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Spatial memory impairments are also observed in self-administrating rats and rats subject to experimenter-led chronic injections (86)(87)(88), with effects lasting up to 3 weeks following abstinence (89). In contrast, a study by Kesby and colleagues (90) found that experimenter-led chronic meth injections may improve learning in mice in a visual discrimination task (90). Taken together, it may be that chronic meth injections may initially improve learning processes but lead to deficits in the long-term, whereas meth self-administration consistently lead to memory impairments.…”
Section: Learning and Memorymentioning
confidence: 98%
“…Spatial memory impairments are also observed in self-administrating rats and rats subject to experimenter-led chronic injections (86)(87)(88), with effects lasting up to 3 weeks following abstinence (89). In contrast, a study by Kesby and colleagues (90) found that experimenter-led chronic meth injections may improve learning in mice in a visual discrimination task (90). Taken together, it may be that chronic meth injections may initially improve learning processes but lead to deficits in the long-term, whereas meth self-administration consistently lead to memory impairments.…”
Section: Learning and Memorymentioning
confidence: 98%
“…In the present model, Tat induction activates astrocytes (as well as bystander microglia) in the striatum ( Bruce-Keller et al, 2008 ; Fitting et al, 2010a ; Zou et al, 2011 ) and causes modest gliosis within 48 h following expression ( Bruce-Keller et al, 2008 ) that can be sustained for as long as 1 year ( Dickens et al, 2017 ). In preclinical rodent studies, CNS exposure to HIV-1 Tat induces behavioral impairments similar to HAND, including deficits in pre-attentive filter processing ( Fitting et al, 2006 ; Paris et al, 2015 ), emotionality ( Fu et al, 2011 ; Hahn et al, 2015 , 2016 ; Lawson et al, 2011 ; Paris et al, 2014 , 2016 ), motivation ( Kesby et al, 2018 ), and memory ( Carey et al, 2012 ; Fitting et al, 2013 ; Marks et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The present study assessed the transcription of dopamine receptor subtypes after three weeks following the completion of doxycycline administration. Therefore, changes in dopamine receptor expression may result from the TAT protein expression and direct effects induced by TAT on molecules of the dopamine system, including alterations in the dopamine transporter and vesicular monoamine transporter-2 [20,40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Conditional TAT exposure in mice has been shown to induce cognitive deficits in a range of behavioural tasks [17,18] and reversal learning appears particularly susceptible to TAT-induced impairments [19,20]. In this model, TAT expression alters dopamine levels [19,21] as well as the expression of the dopamine transporter in the brain [20]. Together, these changes may contribute to the observed reward deficits and increased sensitivity to methamphetamine-induced reward enhancement in the context of TAT expression [21].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation